Peranan Buku Pembantu Sebagai Rincian dari Buku Besar Dalam Menentukan Harga Pokok Produksi (Studi pada Percetakan Andromedia Malang) - Djoko Sugiono (STIE Malangkucecwara, 2015)
Based on the results of analysis, show that the subsedledger is a record of the details in the ledger in the manufacture of products start from production process to become finished products ready to be marketed, where the data is taken from the source. While the ledger containing the total costs incurred in the manufacture of those products where the data is taken from the daily journal that has been recapitulated. Thus it can be said in the manufacture of these products in total costs appear in the ledger, while the details of such costs in the subsedledger, which the company is based on the order subsedledger stated in the cost of the card or charge card. Based on this , management can determine production costs inherent in the order that has already produced, but on the balance sheet date has not been handed over to the buyer, and are presented in the balance sheet as the cost of finished goods inventory. In addition, management can also determine production costs attached to the orders on the balance sheet date still under construction, and is presented in the balance sheet as cost of product inventory in the process.